2020
DOI: 10.3390/plants9091055
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Role of Silicon and Plant–Rhizobacteria Mitigating Abiotic Stresses: A New Approach for Sustainable Agriculture and Climate Change

Abstract: Abiotic stresses are the major constraints in agricultural crop production across the globe. The use of some plant–microbe interactions are established as an environment friendly way of enhancing crop productivity, and improving plant development and tolerance to abiotic stresses by direct or indirect mechanisms. Silicon (Si) can also stimulate plant growth and mitigate environmental stresses, and it is not detrimental to plants and is devoid of environmental contamination even if applied in excess quantity. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 162 publications
(217 reference statements)
1
54
0
Order By: Relevance
“…Silicon might have a positive role in the metabolic activities of plants exposed to salinity stress [ 65 ]. Moreover, it affects plant transpiration rate by silicating the surface of leaves and reducing the stomata lumen [ 38 , 67 ]. Silicon can boost the absorption and translocation of different nutrients [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicon might have a positive role in the metabolic activities of plants exposed to salinity stress [ 65 ]. Moreover, it affects plant transpiration rate by silicating the surface of leaves and reducing the stomata lumen [ 38 , 67 ]. Silicon can boost the absorption and translocation of different nutrients [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the abundance of Si in the soil, most Si is formed as silicon dioxide (SiO 2 ), which is not directly available for plant uptake. Si can improve plant growth, increase crop productivity, enhance photosynthesis efficiency and nitrogen fixation, and ameliorate antioxidant defense systems against various environmental stresses [ 36 , 37 , 38 , 39 ]. Moreover, the accumulation of Si in plant tissues can stimulate the production of phenolics and phytoalexins and can increase pathogen resistance [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, as proposed by Putra et al [ 95 ] an extensive investigation needs to be considered on the cross-talk between Si and legumes to decipher how Si promotes the symbiotic relationship with nitrogen-fixing bacteria. This body of Si is crucial in the future works as numerous studies showed the positive interactive effect of Si and plant growth promoting rhizobacteria on plant growth particularly under unfavorable environmental conditions [ 96 ]. In addition, among the same species, research on genotype-dependent response to Si nutrition need to be considered.…”
Section: Remark and Prospectivementioning
confidence: 99%
“…Silicon (Si) is not regarded as a necessary element for plants; however, some recent studies reported this element to be beneficial for plant growth. Si is one of the most abundant elements in the Earth’s crust and around 70% of soil mass is made up of Si [ 1 , 2 , 3 ]. Exposure to Si imparts uncountable beneficial effects on various plants, especially in gramineous and cyperaceous plants [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nano-SiO 2 -based fertilizers are determined to be beneficial for crops as they minimize fertilizer loss such as nitrogen and phosphorus by controlled release [ 17 ]. The application of SiO 2 -NPs could improve the photosynthetic pigments and increase the photosynthetic rate [ 2 , 3 , 18 ]. It also improved seed germination in Solanum lycopersicum ; the net photosynthetic rate, photochemical efficiency, photosystem II (PSII) activity, electron transport rate, carbonic anhydrase activity, photochemical quenching, stomatal conductance and transpiration rate in Indocalamus barbatus and Cucurbita pepo [ 19 , 20 ]; and it also increased the growth, chlorophyll and carotenoid contents of Solanum tuberosum tubers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%